Strategic Leadership Practices Enhancing Employee Engagement, Innovation, and Sustainable Business Growth Performance - Ratih Astiakurnia Putri; Andi Ihsan Triputrajaya (Mandalika Institute, 2026)
Strategic leadership has become increasingly important in helping organizations navigate dynamic business environments while achieving long-term sustainability. Although previous studies have examined the relationships among strategic leadership, employee engagement, innovation, and organizational performance, these constructs have often been investigated separately, resulting in fragmented theoretical understanding. This study aims to synthesize existing literature and develop an integrated conceptual framework explaining how strategic leadership practices enhance employee engagement and innovation to achieve sustainable business growth performance. Using a qualitative library research design with a systematic literature review approach, the study reviewed and synthesized peer-reviewed publications selected based on their relevance, academic credibility, and alignment with the study's core constructs, including strategic leadership, employee engagement, innovation, and sustainability. The findings indicate that strategic leadership practices foster organizational environments that strengthen employee engagement, stimulate innovation, and enhance organizational adaptability. Employee engagement functions as a key mechanism linking leadership to workforce commitment and innovative behavior, while innovation enables organizations to sustain competitiveness in dynamic environments. Sustainable business growth performance is achieved through the synergistic interaction of leadership, employee engagement, and innovation rather than isolated managerial interventions. The study contributes by proposing an integrated conceptual framework that bridges fragmented literature and provides theoretical insights and practical guidance for leaders seeking to strengthen long-term organizational sustainability.